2018
DOI: 10.1016/s0140-6736(18)30794-3
|View full text |Cite
|
Sign up to set email alerts
|

Determining the worldwide prevalence of obesity

Abstract: number of chronic health conditions that developed per survivor according to a specific timescale (ie, age), taking into consideration multiple and recurrent events and accounting for competing risks. We declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 5 publications
2
104
0
6
Order By: Relevance
“…There are no directly comparable studies in African children, or using the WHO-recommended definition based on BMI, but in non-African populations biases have been reported for other BMI-based definitions of obesity 9 , 10 The present study adds to previous studies suggesting that underestimation of excessive fatness by BMI-for-age criteria is likely to be a global cause for concern 19 , 20 . Our study shows that a high proportion of African children with apparently healthy BMI-for-age have excessive body fatness.…”
Section: Discussionmentioning
confidence: 62%
“…There are no directly comparable studies in African children, or using the WHO-recommended definition based on BMI, but in non-African populations biases have been reported for other BMI-based definitions of obesity 9 , 10 The present study adds to previous studies suggesting that underestimation of excessive fatness by BMI-for-age criteria is likely to be a global cause for concern 19 , 20 . Our study shows that a high proportion of African children with apparently healthy BMI-for-age have excessive body fatness.…”
Section: Discussionmentioning
confidence: 62%
“…Considering gender differences, studies in many regions of the world have shown that, compared to males, females are at greater risk of obesity (15,17). Evidence has confirmed that males and females have differences in anatomical fat distribution, fat utilization, and obesity co-morbidities (18).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has confirmed that males and females have differences in anatomical fat distribution, fat utilization, and obesity co-morbidities (18). These may be rooted in differences in genetics, sex hormones, and even unknown molecular mechanisms (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…This classification is criticized because of the low sensitivity, large interindividual variability in relative body fat, and its attribution to age, sex, and ethnicity. Nevertheless, BMI is the most commonly used instrument in epidemiology and clinical practice due to its simplicity [4,5].…”
Section: Introductionmentioning
confidence: 99%